2020
DOI: 10.1007/s00425-020-03507-x
|View full text |Cite
|
Sign up to set email alerts
|

Inability to accumulate Ni in a genus of hyperaccumulators: the paradox of Odontarrhena sibirica (Brassicaceae)

Abstract: Main conclusion Odontarrhena is a highly diverse genus of Ni-hyperaccumulators. Here, we demonstrate substantial inability to accumulate Ni in the facultative serpentinophyte O. sibirica, which seems a unique case among the numerous species of the genus that grow on ultramafic soils. Abstract Odontarrhena is the most diverse genus of Ni-accumulating plants in W Eurasia, with most taxa growing obligatorily or facultatively on ultramafic soils. A notable exception may be O. sibirica, a facultative serpentinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Adaptations may involve either tolerance or avoidance, such as metal exclusion at the root level, compartmentalization in various plant organs and toxicity tolerance [22]. Some species are able to accumulate over 100 to 1000 times as much metal in their shoots and leaves as their non-hyperaccumulating relatives without displaying toxicity symptoms [22,[28][29][30]. Minimum hyperaccumulation thresholds in plants are defined at 10000, 1000, 300 μg g −1 of leaf dry weight for Mn, Ni and Co, respectively [29].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptations may involve either tolerance or avoidance, such as metal exclusion at the root level, compartmentalization in various plant organs and toxicity tolerance [22]. Some species are able to accumulate over 100 to 1000 times as much metal in their shoots and leaves as their non-hyperaccumulating relatives without displaying toxicity symptoms [22,[28][29][30]. Minimum hyperaccumulation thresholds in plants are defined at 10000, 1000, 300 μg g −1 of leaf dry weight for Mn, Ni and Co, respectively [29].…”
Section: Introductionmentioning
confidence: 99%
“…Such Ni-hyperaccumulators are often obligate endemics of Ni-rich serpentine outcrops, while more rarely they grow either on or off these substrates with, respectively, hyperaccumulating and nonaccumulating populations (Wójcik et al, 2017). So far, the only known exception is O. sibirica, the serpentine populations of which are apparently the only ones in the genus incapable of metal hyperaccumulation (Bettarini et al, 2020). Odontarrhena taxa and populations have been studied as indicators in prospecting for metals (Brooks, 1983), as model systems to investigate the mechanisms of metal-hyperaccumulation (Verbruggen et al, 2009;Deng et al, 2018) and, more recently, as resources for practical applications of metal phytoextraction and agromining (van der Ent et al, 2015;Kidd et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such studies were based on populations of a single species or, in other cases, on one population of two or three distantly related species, sometimes of doubtful taxonomic identification (Cecchi et al, 2018). A recent investigation on O. sibirica provided a more detailed analysis of the Ni-induced stimulation of growth at low metal concentrations (Bettarini et al, 2020). In such study, the metal response in terms of root and shoot growth was found to fit the Brain-Cousens hormetic model (Brain and Cousens, 1989) in serpentine populations of both O. sibirica and O. chalcidica.…”
Section: Introductionmentioning
confidence: 99%
“…As thus construed, the genus Odontarrhena includes 40-50 species of Ni hyperaccumulators [28,[32][33][34][35]. The majority are obligate metallophytes [36,37], but eight or more species are facultative hyperaccumulators [11]. Odontarrhena serpyllifolia (Desf.)…”
Section: Introductionmentioning
confidence: 99%
“…As explained above, the experimental design included non-metallophyte reference species; however, because almost all Odontarrhena spp. are capable of hyperaccumulation [37], it was necessary to use species from other closely related genera in the tribe Alysseae. Two such species were employed, neither of which has been reported to be commonly associated with serpentine or other ultramafic soil [34,42,43,46].…”
Section: Introductionmentioning
confidence: 99%